Performance decrement and skill deterioration during a water polo game are linked with the conditioning level of the athletes - Botonis, P. G.; Toubekis, A. G.; Terzis, G. D.; Geladas, N. D.; Platanou, T. I. (The Journal of Strength and Conditioning Research, 2016)
The aim of the study was to examine whether physical and technical performance deterioration after a water polo game is related to the athletes' conditioning level. Blood lactate concentration was measured during a 5 × 200-m incremental swimming test in 10 male water polo athletes to calculate the velocities corresponding to 4.0, 5.0, and 10.0 mmol7L lactate concentration (V4, V5, and V10, respectively) and define their conditioning level. All athletes participated in 5 competitive water polo games. Before (Pre), at half time (Mid), and after (Post) the first 2 games, handgrip strength and repeated sprint ability (8 × 20-m) were measured. Pre and Post the next 2 games, ball throwing velocity, shooting accuracy, and 400-m swim were evaluated. Pre, Mid, and Post the last game, the eggbeater kick test was performed. Handgrip strength, repeated sprint ability, 400-m swim performance, and ball shooting accuracy decreased after the game (8.4 ± 6.2%, 6.3 ± 3.4%, 7.0 ± 4.1%, and 20.3 ± 23.4%, respectively, p = 0.05). V4, V5, and V10 were not significantly correlated with changes in physical or technical performance after the game. Performance in 400-m swim correlated with V4 and V5 whereas changes in 400-m swim Pre-Post, correlated with changes in ball shooting accuracy and throwing velocity (r = 0.73 and r = 0.80, p = 0.05). These data suggest that V4, V5, and V10 may not correlate with performance decline in water polo. Interestingly, the 400-m swim test is connected with the decline in repeated sprints, ball shooting accuracy, and throwing velocity after a water polo game in well-trained athletes.